Aproximações da função erro de interesse em eletroquímica - Magnani, Romeu [UNESP]; Daun, Gilberto [UNESP]; Benedetti, Assis V. [UNESP] (My University, 1996)
The error function is present in several equations describing eletrode processes. But, only approximations of this function are used. In this work, these and other approximations are studied and evaluated according to precision.
Error function aproximations of interest in Electrochemistry
Keywords: Chronoamperometry; Error function; Power-series expansion